Novel ether and thioether macrocycles from phthalaldehyde. Issue 15 (8th April 2015) - Aitken, R. Alan; Hauduc, Clémence; McLennan, Ross S.; Slawin, Alexandra M.Z.; Wilson, Heather S.
Graphical abstract: Abstract: By reaction of phthalaldehyde (benzene-1, 2-dicarbaldehyde) with ethane-1, 2-diol or 2-mercaptoethanol, macrocycles containing respectively 14- and 12-membered polyether/thioether rings were obtained in low but reproducible yields, and their structures confirmed by X-ray diffraction. The simple compounds (2-vinylphenyl)oxirane and 2-oxiranylbenzaldehyde have also been prepared and characterised for the first time.